Dementia and Falls Management in Underserved Populations: The Cognition and Mobility Care Management Program. Issue 1 (25th September 2020) - Tan, Zaldy S.; Hamade, Wael; Menkin, Josephine; de Pacheco, Renee Guillen; Gans, Daphna; Weintraub, Nancy; Garcia, Maribel; Guerrero, Lourdes R.; Reuben, David B.
Abstract : BACKGROUND/OBJECTIVES: Cognitive and mobility impairments are common and underdiagnosed chronic conditions that afflict community‐dwelling older adults. This study describes the organization, implementation, and evaluation of an intervention for underserved and ethnically diverse older patients with dementia and/or falls risk. DESIGN: Observation, baseline and 1 year after intervention. SETTING: Community‐based primary care county clinics in inland southern California. PARTICIPANTS: A total of 272 persons, aged 70 years and older, who screened positive for falls and/or dementia and enrolled in the Cognition and Mobility Care Management program during the study period. INTERVENTION: A nurse care manager performed a patient and caregiver evaluation and created and implemented a care plan with medical, behavioral, and psychosocial interventions in partnership with patients and their primary care providers. MEASUREMENTS: Process outcomes included rates of positive screening for dementia and fall risk, referral, enrollment, and visit completion. Patient outcomes included fall history, mobility and cognitive assessments, and depression scales. Patients and/or caregivers completed questionnaires rating perceived benefits of enrollment after 1 year in the program. RESULTS: Medical assistants screened 573 patients aged 70 years and older during the study period; 78% screened positive for dementia and/or fall risk. Of the patients who screened positive, 94% were referred; 91% of contacted patients elected to enroll, and 272 patients completed an intake visit (meanage = 77 years; 65% female; 75% Latino; 10% African American). The patients and caregivers who completed satisfaction questionnaires 1 year after enrollment rated the program highly, and 92% would recommend the program to others. CONCLUSION: A primary care–based screening and comanagement program to identify and manage dementia and falls risk in primarily Latino and African American older adult patients living in an underserved area was well received, with high satisfaction and perceived benefit from patients and caregivers.